Exchange Rate Changes and Philippine Fresh Mango Export Volume to Hong Kong: A Monthly Time-Series Analysis (2015 – 2025) - Nathaniel Panganiban; Felicity Mae A. Bondoc; Hannah May H. Oriño; Jhizeth Ann B. Rivera; Louisa Rafaelle L. Ybañez (Future Science / FSH-PH Publications, 2026)
The study examined the effect of changes in exchange rate between Philippine peso and Hong Kong dollar to the volume of Philippine fresh mangoes exported to Hong Kong given its perishable nature and demand for the country. The study applied time-series analysis using a total of 132 observation collected from January 2015 to December of 2025. The data underwent a logarithmic transformation, stationary testing, and differencing. Additionally, the study used the ordinary least squares (OLS) method for regression and include seasonal dummy variables. The findings revealed that changes in exchange rate had a positive effect on the export volume of fresh mangoes, however, the result is statistically insignificant (p=0.826). Seasonal factors were found to be more influential, with export quantity significantly higher in April and May. The model explained about 28.8 percent of the variation in export volume. These finding tells that short-term changes in exchange rate were not the main factor of mango export performance during the studied period. Instead, timing of harvest and supply availability played more important role. The findings suggests that exporters and policymakers should focus more on harvest time and shipping logistics instead of short-term exchange rates.